Patient-reported continuity of care and the association with patient experience of cardiovascular prevention: an observational study in Germany - Arnold, Christine; Hennrich, Patrick; Wensing, Michel (BMC primary care, 2022)
Cardiovascular diseases are often accompanied by comorbidities, which require good coordination of care. Especially in fragmented healthcare systems, it is important to apply strategies such as case management to achieve high continuity of care. The aim of this study was to document continuity of care from the patients’ perspective in ambulatory cardiovascular care in Germany and to explore the associations with patient-reported experience of cardiovascular prevention.
Gesehen am 20.07.2022